Deconstruction in the Maʿnā-Cum-Maghzā Method and Linguistic Hermeneutics: A Comparative Analysis of Qur'anic Interpretative Approaches - Mually, M. Ajril; Abdulghani, Naser Ali (Al-Karim: International Journal of Quranic and Islamic Studies, 2024)
This study aims to analyze the aspects of deconstruction in the Ma'na Cum Maghza method developed by Sahiron Syamsuddin and the Linguistic Hermeneutics introduced by Arkoun. It identifies the extent to which these two methods adopt a deconstructive approach in Qur'anic interpretation, particularly in linguistic aspects, and compares the characteristics of deconstruction within them. This research employs a comparative analysis method using a library research approach, where data is collected from various relevant sources. Three main questions form the foundation of this study: (1) How are Ma'na Cum Maghza and Linguistic Hermeneutics applied in Qur'anic interpretation through a linguistic approach? (2) What makes these two methods deconstructive? (3) How do the concepts of deconstruction in these two methods compare? The findings indicate that both Ma'na Cum Maghza and Linguistic Hermeneutics contain certain methodological aspects that are deconstructive. However, this study also reveals that neither method can be fully categorized as entirely deconstructionist. Several aspects contradict the principles of deconstruction, such as the tendency of Ma'na Cum Maghza towards contextualization and the structuralist approach employed in Arkoun's Linguistic Hermeneutics. Thus, Sahiron Syamsuddin and Arkoun are not radical proponents of deconstructive reading in their interpretative methods. The theoretical implication of this research is that it provides a conceptual mapping of the application of deconstruction in contemporary Qur'anic studies and clarifies the boundaries between interpretative methods that are truly deconstructive and those that only adopt certain deconstructive principles. Contribution: This study contributes to the development of Qur'anic interpretation and hermeneutics by offering a more critical perspective on linguistically-based interpretative methods in Islam.